Pengaruh Mekanisme Corporate Governance Terhadap Nilai Perusahaan Dengan Kinerja Variabel Intervening - Eka Sariningsih (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2016)
This Research was conducted to look at the Corporate Governance Mechanism wheather itsaffected the corporate value where performance as intervening variabel. The reserach was anexplanatory research approach. The sample was taken by the purposive sampling method by certaincriteria the regression analysis was employed to find out whether the corporate governancemechanism affects the performance, and corporation value. The results from path analysis indicatedthat corporate governance directly affected the corporation value but indirectly affected theperformance and the corporation value.